A Comparison of Treatment Options for Carpal Boss: A Critically Appraised Topic - Megan Collins; Matthew Rivera (Bowling Green State University, 2021)
Context: Carpal bossing is a bony growth or mass that typically occurs at the 2nd or 3rd carpometacarpal joint. Carpal bossing is often overlooked placing the patient at an increased risk for pain or injury, such as osteoarthritis or inflammatory joint disease if left untreated. Individuals such as combat sport athletes who experience repetitive trauma to this area are at a high risk to develop carpal bossing. The literature suggests conservative or surgical interventions to manage symptoms. The goal of this systematic review is to synthesize the current literature for clinical knowledge and intervention outcomes for carpal bossing. Methods: A systematic search of the literature was performed across 3 electronic databases (Science Direct, PubMed, and EBSCOhost) to identify articles that investigated the effects of surgical intervention or conservative management for carpal bossing. A combination of the keywords and Boolean operators (Carpal Bossing, Carpal Boss, Surgical Intervention, Wedge Resection, Excision, Conservative Treatment, and Intervention) related to the research question were used. The search was restricted to full text, human studies (including cadaveric studies) research, and manuscripts available in English. Articles were included if they examined the effect of either conservative or surgical interventions for the treatment of carpal bossing. Articles were excluded from the review if the study did not examine carpal bossing treatment options or did not include pain, range of motion, strength, or functional measures of the hand and wrist. Two independent reviewers used the Joanna Briggs Institute Checklist for Case Reports and the Checklist for Case Studies to appraise the quality of the articles. A score of 50% was used to remove low-quality studies. The Strength of Recommendation Taxonomy (SORT) method was used to grade the evidence for the articles included. Results: After the initial search, 10 articles met the inclusion criteria, while 3 were eliminated due to low quality appraisal scores. The average scores for case reports and case studies were 5.5/7 or 7.5/9 respectively. There was a total of 58 participants across the 7 studies. Generally speaking, conservative treatment reduced average daily pain and patients were able to return to full participation within 2 weeks. Conversely, patients undergoing surgical intervention experienced episodic pain, including over the surgical incision, typically averaging 2/10 on the visual analog scale. Findings from the surgical intervention showed inconsistent measurements for wrist/hand strength and range of motion. There is level C evidence on the treatment for carpal bossing. Conclusion: The limited evidence suggests conservative management may reduce pain and improve clinical outcomes. However, clinicians should consider the level C evidence with skepticism as the quality of evidence on this topic is low. Further investigations should be performed with more rigor.